BAHAYA LIMBAH INDUSTRI TERHADAP KEBERLANGSUNGAN HIDUP MANUSIA - Ardian Hangga Kelana; Titia Erika Sarlota Awom; Saul Weipsa; Yekson Soll; Evellyne Binsyowie Sandhiya Mandosir (Bajang Institute, 2025)
This community service activity (PKM) aims to provide information and knowledge about